Mutations in the cationic trypsinogen gene and evidence for genetic heterogeneity in hereditary pancreatitis. Issue 3 (1st March 1999) - Férec, C; Raguénès, O; Salomon, R; Roche, C; Bernard, J P; Guillot, M; Quéré, I; Faure, C; Mercier, B; Audrézet, M P; Guillausseau, P J; Dupont, C; et al.
Abstract : Hereditary pancreatitis (HP) is a rare inherited disorder, characterised by recurrent episodes of pancreatitis often beginning in early childhood. The mode of inheritance suggests an autosomal dominant trait with incomplete penetrance. The gene, or at least one of the genes, responsible for hereditary pancreatitis has been mapped to the long arm of chromosome 7 and a missense mutation, an arginine to histidine substitution at residue 117 in the trypsinogen cationic gene (try4) has been shown to segregate with the HP phenotype. The aim of this work was to investigate the molecular basis of hereditary pancreatitis. This study was performed on 14 HP families. The five exons of the trypsinogen cationic gene were studied using a specific gene amplification assay combined with denaturing gradient gel electrophoresis (DGGE). The present paper describes three novel mutations, namely K23R and N29I and a deletion –28delTCC in the promoter region. We also found a polymorphism in exon 4, D162D. In eight of these families we found a mutation which segregates with the disease. A segregation analysis using microsatellite markers carried out on the other families suggests genetic heterogeneity in at least one of them. Our findings confirm the implication of the cationic trypsinogen gene in HP and highlight allelic diversity associated with this phenotype. We also show that the pattern of inheritance of HP is probably complex and that other genes may be involved in this genetic disease.